2022
DOI: 10.3390/biology11050795
|View full text |Cite
|
Sign up to set email alerts
|

GJB2 Is a Major Cause of Non-Syndromic Hearing Impairment in Senegal

Abstract: This study aimed to investigate GJB2 (MIM: 121011) and GJB6 (MIM: 604418) variants associated with familial non-syndromic hearing impairment (HI) in Senegal. We investigated a total of 129 affected and 143 unaffected individuals from 44 multiplex families by segregating autosomal recessive non-syndromic HI, 9 sporadic HI cases of putative genetic origin, and 148 control individuals without personal or family history of HI. The DNA samples were screened for GJB2 coding-region variants and GJB6-D3S1830 deletions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Contrasting with reports from other SSA countries, where environmental factors remain a major cause of CHI, our study revealed a higher proportion of likely genetic etiology (52.7%), which is similar to reports from high-income settings [ 27 , 28 ]. This discrepancy might be due to the high consanguinity rate associated with a significant contribution of GJB2 to NSHI in the Senegalese population [ 22 ]. Moreover, Senegal is in an epidemiological transition phase characterized by the reduction of infectious diseases [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrasting with reports from other SSA countries, where environmental factors remain a major cause of CHI, our study revealed a higher proportion of likely genetic etiology (52.7%), which is similar to reports from high-income settings [ 27 , 28 ]. This discrepancy might be due to the high consanguinity rate associated with a significant contribution of GJB2 to NSHI in the Senegalese population [ 22 ]. Moreover, Senegal is in an epidemiological transition phase characterized by the reduction of infectious diseases [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is not yet a universal newborn hearing screening program in Senegal. We recently showed that variants in GJB2 explained HI in 34.1% of the cases ( n = 15/44) in a select group of multiplex families in Senegal [ 22 ]. In order to get the full spectrum of CHI-associated etiologies across the country, we extended our recruitment to determine the clinical characteristics of CHI in Senegalese individuals living with HI.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, recently, mutations in the GJB2 gene were confirmed in NSHI in Senegal. 8 The genetic diversity of Africans and the complexity of the etiologies of HI cases could be contributing to the variability in detecting common NSHI causal mutations. 9,10 Nonetheless, the detection of novel genes for HI will benefit future initiatives regarding prevention, treatments, cure, care, or genetic counselling targeted towards Africans.…”
Section: Introductionmentioning
confidence: 99%
“…These variants account for most cases of NSHI in European and Asian populations but are rarely identified in SSA 7 . However, recently, mutations in the GJB2 gene were confirmed in NSHI in Senegal 8 . The genetic diversity of Africans and the complexity of the etiologies of HI cases could be contributing to the variability in detecting common NSHI causal mutations 9,10 .…”
Section: Introductionmentioning
confidence: 99%